INTEGRATION OF ARTIFICIAL INTELLIGENCE IN RISK MANAGEMENT TO IMPROVE BUSINESS SUSTAINABILITY - Franciskus Antonius Alijoyo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The integration of artificial intelligence (AI) in risk management offers a significant improvement in a company's ability to identify and handle risks more efficiently and accurately. AI enables in-depth and predictive data analysis, so that organisations can detect potential threats earlier and take proactive measures to mitigate them. The result is more efficient operations and more sustainable strategies. However, the successful implementation of AI in risk management requires employee training and the ethical use of this technology. With the right preparation, AI can play an important role in improving business sustainability and competitiveness.